Risk, Network Quality, and Family Structure : Child Fostering Decisions in Burkina Faso - Richard Akresh (Institute for the Study of Labor (IZA), 2005)
Researchers often assume household structure is exogenous, but child fostering, the institution in which parents send their biological children to live with another family, is widespread in sub-Saharan Africa and provides evidence against this assumption. Using data I collected in Burkina Faso, I analyze a household's decision to adjust its size and composition through fostering. A household fosters children as a risk-coping mechanism in response to exogenous income shocks, if it has a good social network, and to satisfy labor demands within the household. Increases of one standard deviation in a household's agricultural shock, percentage of good network members, or number of older girls increase the probability of sending a child above the current fostering level by 29.1, 30.0, and 34.5 percent, respectively. Testing whether factors influencing the sending decision have an opposite impact on the receiving decision leads to a rejection of the symmetric, theoretical model for child fostering.
Keywords: J12; O15; D10; 330; child fostering; risk-coping; social networks; household structure; Familie; Kinderbetreuung; Soziales Netzwerk; Burkina Faso